Risk factors assessment for Type-II Diabetes Mellitus - Adak, M; Nazri, S (Journal of Institute of Medicine Nepal, 2009)
Some of the tables and figures are missing from this article. See Vol.31(1) p.42-43 for the missing information. Introduction: Diabetes mellitus is a group of metabolic abnormality often deliberating with sever complications of retinopathy, nephropathy and microangiopathy, which is one of the most common endocrine disorders in all populations and all age groups. Materials and Methods: This is a retrospective study. A total of 1118 adult subjects were enrolled in the OPD in NMCTH. The case records of the patients of both genders aged range from 20-70 years. A definitive diagnosis was made based on clinical features, fasting blood sugar, post- Prandial blood sugar and lipid profiles estimation. Results: Out of total patients, 142 were male and 71 were female Type -II diabetes patients. Male diabetes was maximum in 41-50 years age groups. Associated risk factors and co-morbid conditions were analyzed. Factors like physical activity, socio-economical status, family history, obesity have shown statistically significant association with diabetes mellitus. About 42% have systolic BP> 140 mm of Hg and 47% have diastolic BP> 80 mm of Hg. Conclusion: This study showed a trend of diabetes with age in both sexes, reaching the highest in the age 41-50 years. Based on our study, we may concluded that these factors need to be addressed in prevention and control strategies in this area. Key words: Type-II diabetes mellitus, blood sugar level, hypertension, dyslipidemia. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 23-30